The identification of alternative principal licensing policy elements and issues: perceptions of Colorado superintendents and principals - Hickey-Gramke, Michelle, author; Whaley, David C., advisor; Lehmann, Jean P., committee member; Spencer, Karen C., committee member; Gloeckner, Gene W., committee member (Colorado State University. Libraries, 2006)
Given the high stakes accountability that exists today for student success and the responsibility for ensuring a faculty of highly qualified teachers (No Child Left Behind Act, 2001), the role of the school administrator is significantly more challenging and complex (Glickman, 2001) than in the past. In these particularly demanding times, the issue of administrator shortages in school districts has intensified and alternative principal licensing has emerged as a viable option. Given these needs, this investigation followed three lines of inquiry: (a) an examination of state policies related to principal alternative certification programming; (b) an analysis of the information gathered from an expert panel in education; and (c) a study of how superintendents and principals in public education perceived this information related to principal alternative certification policy. The first line of inquiry was conducted through a nation-wide survey. All 50 state licensing agencies were contacted in an effort to determine those states with an alternative principal licensing policy and then to discern the essential elements of each particular policy. Using the state licensing policy elements determined through the initial inquiry process, efforts were undertaken as a part of the second portion of this research to pattern code the various state licensing policy elements into nine representative categories. This second line of inquiry was carried out using an expert panel of Colorado superintendents and principals. The third line of inquiry was conducted using a two round modified Delphi of Colorado public school superintendents and principals. This study has extended the current knowledge of alternative principal licensing policy and has generated nine categories that school districts and state licensing agencies can use as a foundation to begin or modify their alternative principal licensing policy. The nine categories include: application, review panel, education requirements, work experience, induction, internships, license length, mentoring, and testing.
Keywords: school administration; educational administration